Pr-Si co-doped IrOx as promoted anode for refractory SDZ degradation - Sun, Cancan; Chen, Xiaodan; Ma, Chenglong; Cao, Limei; Yang, Ji (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2021)
Electrochemical oxidation technology has been used in treating bio-refractory organic effluent. However, the energy consumption is subject to the high oxygen evolution potential (OEP) of the traditional electrode. Doped Ir-contained oxides electrode is capable of degrading pollutants efficiently at low energy consumption. In this study, a facile (Ir0.4Pr0.4Si0.2)Ox electrode was prepared using the thermal decomposition method, which exhibits a larger electrochemical surface area (ECSA, 287.71 cm2) and tunnel structures caused by Pr and Si’s leaching. The (Ir0.4Pr0.4Si0.2)Ox electrode was applied to degrade sulfadiazine (SDZ). The parameters of the initial concentration of SDZ, electrolyte concentration, pH, and the applied voltage on SDZ removal were investigated. The optimal condition was explored, and the SDZ degradation efficiency reached 100% within 2 h. We attribute the excellent degradation performance to the presence of tunnel structures on the electrode, which promotes the generation of ·O2− and ·OH. An indirect electrochemical oxidation mechanism is proposed according to the identification of the intermediate through the LC-MS. The novel electrode achieved in this work is promising to treat acid SDZ wastewater in the electrochemical system.